2011
DOI: 10.1021/jo2002769
|View full text |Cite
|
Sign up to set email alerts
|

Nano Sulfated Titania as Solid Acid Catalyst in Direct Synthesis of Fatty Acid Amides

Abstract: Nanosized sulfated titania was prepared by a sol-gel hydrothermal process. X-ray diffraction (XRD), transmission electron, and scanning electron micrographs (TEM and SEM), FT-IR specific surface area, and BET N(2) adsorption were employed to characterize the properties of the synthesized sulfated TiO(2). The results indicate that both anatase and rutile TiO(2) are obtainable. This prepared sulfated titania showed high catalytic activity in direct amidation of fatty acids as well as benzoic acids with various a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(42 citation statements)
references
References 51 publications
0
38
0
Order By: Relevance
“…The broader band at 3,460 cm -1 is attributed to the stretching vibration and bending vibration of hydroxyl groups on TiO 2 [27,28]. Another peak at 1,630 cm -1 is attributed to the bending vibration of H-O-H on absorbed water [29]. In Fig.…”
Section: Uv-vis Spectra Analysismentioning
confidence: 85%
“…The broader band at 3,460 cm -1 is attributed to the stretching vibration and bending vibration of hydroxyl groups on TiO 2 [27,28]. Another peak at 1,630 cm -1 is attributed to the bending vibration of H-O-H on absorbed water [29]. In Fig.…”
Section: Uv-vis Spectra Analysismentioning
confidence: 85%
“…Alternatively, few more formylating reagents like acetic formic anhydride, ammonium formate, activated formic esters, chloral, imidazole-DMF and catalysts VB 1 , Zn metal, ZnO with formic acid may be used [34][35][36][37][38]. Many other useful catalysts such as aqueous formaldehyde-iridium, CeO 2 -formic acid, imidazoliumbased ionic liquid CO 2 , and stearic acid-nanosulphated TiO 2 have been reported [39][40][41][42][43]. However, many of these procedures su er from the di culties such as high toxicity, expensive reagents, prolonged reaction time, and issues associated with impurities, which need further puri cation and require special care.…”
Section: Introductionmentioning
confidence: 99%
“…To increase the reaction rate, many metal oxides demonstrated catalytic activity such as CeO2, CaO, MgO, ZnO, Y2O3, TiO2, ZrO2, Nb2O5, Al2O3, SiO2 10-13 as well as solid acids like Amberlyst-15, HBEA, niobic acid, mont-K10, nafion-SiO2 and IBA 10,14 . Among them, titania provides a unique combination of low price and high catalytic activity [15][16][17] . Hosseini-Sarvari et al 15 applied nanosized sulfated titania to direct amide synthesis in a batch reactor using a wide range of substrates and obtained the yields of 70 -98 % in 3 -12 h at 115 ºC.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, titania provides a unique combination of low price and high catalytic activity [15][16][17] . Hosseini-Sarvari et al 15 applied nanosized sulfated titania to direct amide synthesis in a batch reactor using a wide range of substrates and obtained the yields of 70 -98 % in 3 -12 h at 115 ºC. Nagarajan et al 16 demonstrated quick (under 30 min) amide synthesis with the yields ranging from 83 to 98 % using sulfated titania nanotubes at 110 ºC.…”
Section: Introductionmentioning
confidence: 99%